Scoping review of grief studies in Indonesia - Christina Yeni Kustanti; Nurlia Ikaningtyas; Ninik Yunitri; Hidayat Arifin; Mei Rianita Elfrida Sinaga; Eka Kristina Asi; Nimsi Melati; Henny Dwi Susanti (Faculty of Nursing Universitas Padjadjaran, 2023)
Background: One death can cause nine bereavements. Considering the impact of human loss, studies on grief are crucial for better bereavement care services. Purpose: This study examined studies on grief conducted in Indonesia. Indonesian grief research mapping will identify study gaps and suggest further research. Methods: The reporting for a scoping review adhered to the PRISMA (preferred reporting elements for systematic review and meta-analysis) statement for a scoping review. A systematic screening was performed in MedLine, Embase, CINAHL, Web of Science, Scopus, and PubMed, as well as manual searches via Google Scholar, Portal Garuda, and relevant studies without language and date restrictions. The data retrieved in the literature were analyzed descriptively, and the themes were developed using NVivo software. Results: Based on the 18 included studies, the types of grief studies in Indonesia can be divided into pre- and after-loss grief areas. Regarding the themes of the studies that have been conducted in Indonesia, five themes can be derived, related to (1) study purposes, (2) cause of grief, (3) population, (4) concept being studied, and (5) outcomes being studied. Conclusion: There is significant room for growth in the grief research field in Indonesia. It will be vital for researchers in Indonesia to perform additional studies on pre-loss grief, other studies connected to interventional trials, and further studies examining variation in the outcomes.